PENGAWETAN DAN PENGOLAHAN LIMBAH IKAN SERTA IKAN SEGAR MENJADI PRODUK YANG DAPAT MENINGKATKAN PENDAPATAN KELUARGA NELAYAN DI KELURAHAN MALABRO KOTA BENGKULU - Hatta, Madani; ., Halimatusyadiah; Sari, Novita (Dharma Raflesia : Jurnal Ilmiah Pengembangan dan Penerapan IPTEKS, 2014)
This program is a community service activities with the activity of the title is Preservation and Processing of Fish Waste and Fresh Fish that can be Income Generating Products for Fishermen Household in Village Malabro Bengkulu. This activity aims to equip the housewives of fishermen about fish preservation and processing of fish waste into products that can be sold to raise additional revenue for fishermen family in the village of Malabro. The results achieved from this activity is fishermen housewives have gained new knowledge about fish preservation and processing of fish waste into fish crackers, fishermen housewives eager and motivated to immediately apply the knowledge and skills gained from this activity, establishment of home industry by housewives of fishermen engaged in the processing of fish crackers processed fish waste, fishermen housewives have been able to preserve the fish in order to survive longer, fishermen housewives have learned how to market their product or distributed crackers they made, which has been formed a new source of income for women in the fishing village Malabro. Keyword: Preservation, Processing, Fish Waste, Fish Crackers